Evaluation of caries risk reduction following preventive programs in orthodontic patients, using Cariogram computer model: A quasi-experimental trial - Maryam DOOST-HOSEINI; Massoud SEIFI; Mina PAKKHESAL; Abolfazl SABOURY; Parisa AMDJADI; Aliakbar NAGHAVIALHOSSEINI (Dental Press Editora, 2021)
ABSTRACT Objective: This study evaluated the effectiveness of preventive strategies on caries risk reduction in patients undergoing orthodontic treatment, using the Cariogram program. Methods: In this quasi-experimental study, samples were selected using a convenience quota sampling technique, in a public dental school. At first, caries risk profile was determined for each subject using the Cariogram before brackets bonding. The sample size consisted of 36 patients. The intervention group (n = 18) received preventive programs, and the control group (n = 18) was trained based on the routine oral health education by means of pamphlets. Then, Cariogram parameters were calculated for patients in both groups after six months. Results: The age range of participants was from 12 to 29 years. The mean percentage of the "Actual chance of avoiding new cavities" section in the intervention group increased from 45.72 ± 21.64 to 62.50 ± 17.64. However, the mean percentage of other parameters - such as "Diet", "Bacteria" and "Susceptibility" - decreased after six months (p< 0.001). Besides, the differences in the mean percentage between intervention and control group at the end of the study period (T1) related to the Cariogram parameters were statistically significant (p< 0.001). Accordingly, the mean percentage of 'Actual chance of avoiding new cavities'' parameter in the intervention group (62.50) was statistically higher than in the control group (42.44) (p< 0.001). Conclusion: Implementing different preventive approaches is able to reduce the caries risk in patients undergoing fixed orthodontic treatment, which can be clearly demonstrated using Cariogram program.